TECHNOLOGY OF INCREASING THE EFFICIENCY OF COMPETITIVE ACTIVITY AND DEVELOPING STRENGTH ENDURANCE OF ATHLETES IN SPORTS WRESTLING (Scientific journal of the Fergana State University, 2023)
This article presents information about the effectiveness of the development of endurance qualities, determination of the level of muscular strength of wrestlers with the help of special sports equipment, as well as the strength of qualified wrestlers engaged in wrestling developed in our country, such as: freestyle wrestling, Greco-Roman wrestling, belt wrestling, judo and sambo.